THE INFLUENCE OF SHOPEE BRAND LEADERSHIP ON CUSTOMER LOYALTY WITH CUSTOMER SATISFACTION AS INTERVENING VARIABLE - Fayza Najeela Pakutandang; Indrawati Indrawati (LPPM STIE Muhammadiah Bandung, 2022)
This study aims to explain how Shopee's brand leadership is and how customers feel in terms of satisfaction and loyalty to the Shopee application. Additionally, it seeks to understand how brand leadership affects satisfaction and loyalty and how satisfaction variables mediate this effect. This study uses quantitative methods with causal and descriptive analysis. Data was collected using a questionnaire distributed to Shopee users in Indonesia. 275 samples were collected and analyzed using SmartPLS 3.0, also used descriptive analysis. Based on descriptive analysis findings, the brand leadership dimensions, satisfaction, and loyalty are in good category. PLS-SEM results show brand leadership has a positive and significant effect on satisfaction. The variables of quality, value, and satisfaction have a positive and significant effect on loyalty, whereas innovativeness and popularity not. Additionally, satisfaction acts as a mediator in the relationship between brand leadership and loyalty.